2014
DOI: 10.1093/ejo/cju028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of St John's wort on bone formation in the orthopaedically expanded premaxillary suture in rats: a histological study

Abstract: Although more effective in long-term usage, systemic use of St John's wort hastens new bone regeneration at the premaxillary suture and may help prevent relapse after expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Compared with previous studies that tested plants with high antioxidant capacities such as Urtica dioica, 8 Ginkgo biloba, 11 and Hypericum perforatum, 12 the change in the number of osteoclasts and osteoblasts was similar to the current study. However, these plant extracts are made up of various components and, given the difficulty in obtaining scientific evidence, it was unclear which component has the greatest effect on bone formation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Compared with previous studies that tested plants with high antioxidant capacities such as Urtica dioica, 8 Ginkgo biloba, 11 and Hypericum perforatum, 12 the change in the number of osteoclasts and osteoblasts was similar to the current study. However, these plant extracts are made up of various components and, given the difficulty in obtaining scientific evidence, it was unclear which component has the greatest effect on bone formation.…”
Section: Discussionsupporting
confidence: 83%
“…The number of animals used in this study was lower than some previous studies. [7][8][9][10][11][12] For ethical reasons, the number of animals approved for scientific experiments must be justified and reasonable. 24 In this study, after the statistical power analysis, the number of animals was reduced to the minimum required to achieve a scientific goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal cells located on the inner side of the cartilaginous tissue proliferate and differentiate into osteoblasts when the suture is expanded ( 5 ). Many new materials especially antioxidants were used in studies and showed that antioxidants increases the osteoblastic activity and bone metabolism ( 6 - 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Водный экстракт надземной части активировал регенерацию костной ткани при расширении среднего небного шва, проводимого при коррекции прикуса [156]. В эксперименте показано, что стандартизированный метанольный экстракт восстанавливал костные ткани челюсти на модели стресса [157], этанольный экстракт активировал восстановление клеток пульпы зубов [158], масляный экстракт способствовал заживлению костной ткани при внедрении трансплантата [159].…”
Section: эффективность экстрактов H Perforatum при поражениях челюстно-лицевой областиunclassified